Short Term Investigation on Sulphate Resistance of Oil Palm Shell Lightweight Aggregate Concrete Containing Palm Oil Fuel Ash as Partial Cement Replacement - Khairunisa, Muthusamy; Nur Azzimah, Zamri (Maxwell Scientific Organization, 2015)
This research aims to produce an environmental friendly oil palm shell lightweight aggregate concrete containing palm oil fuel ash of good strength and durability against sulphate attack which is suitable to be applied in construction industry. This study discusses the performance of oil palm shell lightweight aggregate concrete containing palm oil fuel ash as partial cement replacement in sulphate environment. Concrete cubes produced using ranges of palm oil fuel ash from 0 to 40% were water cured for 28 days before tested for determination of compressive strength. The compressive strength test was conducted in accordance to BS EN 12390:3. Sulphate resistance test was conducted on plain specimen and mix containing 20% POFA which strength performance is the best. Both specimens were immersed in sodium sulphate solution for 45 weeks. The results indicate integration of suitable percentage of palm oil fuel ash enhances the compressive strength and sulphate resistance of oil palm shell lightweight aggregate concrete. Inclusion of this ash consumes calcium hydroxide through pozzolanic reaction generating secondary calcium silicate hydrate gel thus assisting the concrete to be denser, stronger and more resistance to sulphate attack compared to plain specimen.